Critical epistemological teleology of bioecotoxicomonitors in aquatic ecotoxicology - Argota-Pérez, George (2024)
The selective interpretation of pollution data in a river impedes the precise and comprehensive understanding of environmental impact. Th e aim was to delineate the epistemological critical teleology of bioecotoximonitors in aquatic ecotoxicology. The application of epistemological critical teleology in aquatic ecotoxicology is paramount for a deeper and more eff ective comprehension of environmental challenges. This perspective transcends mere data accumulation, focusing on introspection regarding the purposes and meanings behind scientific inquirí. Bioecotoximonitors are not merely data collection tools but rather represent an opportunity to comprehend the interaction between living organisms and their surroundings. By establishing correlations between contaminant exposure and biological responses, they enable the projection of potential future scenarios and the design of more effective and sustainable management strategies. This perspective fosters a more contemplative and ethical science, oriented toward environmental sustainability. It is concluded that epistemological critical teleology steers the bioecotoximonitor toward bias minimization and selective explanation, thereby promoting scientific objectivity.